Proposed new interior design of Justlife retail for Justlife Group Sdn. Bhd. at Lot 8-1-1-16 & B-1-1-18, First Floor, BBT One Boulevard, Lebuh Batu Nilam 2, Bandar Bukit Tinggi, 41200, Klang Selangor / Nur Kamaliyah Mohd Kamal - Mohd Kamal, Nur Kamaliyah (Faculty of Architecture, Planning and Surveying, 2010)
Every Interior Design student is required to prepare one final year project. it compulsory to get graduated successfully. The selection of the project must be related closely to current issues or similar to it. So that student easier to find a sources. The knowledge and skill are important along the process of design work which is research,case study,designing proposal,submission by stage,create session,presentation drawing,design development and last but not least final presentation.The client of this project is is Justlife Group Sdn. Bhd. The idea come when the global warming is one of the most critical issue nowadays. The reason to proposed this project at at Lot B-1-1-16 & B-1-1-18,1st Floor,BBT One Boulevard,Lebuh Batu Nilam 2,Bandar Bukit Tinggi,41200 Klang, Selangor because there no one Justlife branch at Klang area. Concept and image that had been chosen not only must be suitable with the product,but it must have a strong impact to the design. From the resesrch and observation based on the product and site,the information and detailing gathered used as a guideline to do the design. The objective of the project is to design a sustainable design that can attract youngster to join save the earth and it can satisfy the client needs. It is sincerely hoped that the project can do well.